Growth Rate of Staghorn Coral (Acropora) on Coral Garden Program at Sempu Nature Reserve Malang - Oktiyas Muzaky Luthfi; Novita Nurmalasari; Alfan Jauhari (Research Journal of Life Science, 2015)
Live coral cover at Sempu Nature Reserve was decrease from 50% in 2006 to 36% in 2013. Adverse human activities such as: over-fishing, recreational activities, waste disposal, deforestation, reef mining and deforestation were suggested to be main factors for declining coral reef at this area. Restoration is defined as the act of returning an ecosystem, as nearly as possible, to its original condition. Coral on Sendang Biru laid on northern area of Sempu Island. Coral garden was establish in the end of 2013. Aim of this research was to know the growth (wide, number of branches, growth rate) of staghorn coral that was transplanted on steel frame at coral garden in different depth. Staghorn coral were tied on doom shaped steel in 6 m depth. The result showed that the average of increasing staghorn coral's area was 56. 91 cm2, number of branch increase was 55 and growth rate was 5.23 cm2/month respectively. Increase of depth will influence to decrease of sunlight intensity in water will be affected on calcification rate of coral. GR of staghorn coral in Sempu was higher than other area.